Developing the next generation of treatment flowsheets for rural wastewater - Brown, Gareth (Cranfield University, 2022)
Septic tank systems (STS) are one of the most common wastewater treatment systems in the world however these systems are becoming antiquated, struggling to meet tighter consent, needing frequent desludging and venting greenhouse gases to the environment. A flowsheet to tackle these issues was proposed consisting of an enhanced septic tank (EST) and a constructed wetland (CW). The proposed flowsheet was assessed by examining the underlying mechanisms, testing the flowsheet at pilot scale and assessing the cost and carbon implications of the flowsheet. A key aim of the thesis is to decrease the maintenance of the flowsheet to once every 5 to 7 years. The maintenance of septic tank is due to desludging, as the tank needs to be emptied when the sludge bed reaches a certain height. The desludging of a septic tank is dependent on the hydrolysis rate within the reactor. Batch studies into anaerobic digestion found that low operating temperatures in septic tanks impact the hydrolysis rate. However, temperature is not the dominant factor of hydrolysis and optimisation of mass transfer between hydrolytic microorganisms and degradable particulates can increase the hydrolysis rate by 200%. A pilot scale study investigated using baffles to promote hydraulic mixing within a septic tank. The presence of hydraulic mixing due to the baffles increased the hydrolysis rate constant of a septic tank from 0.0089 d⁻¹ to 0.035d⁻¹, extending the time between desludging from 4.9 to 6.7 years. The proposed flowsheet is a lower cost treatment system than a conventional package treatment system (e.g. submerged aerated filter) over a 30 year life time and leads to a significant reduction in lifetime carbon emissions compared to a STS. The cost and carbon reduction of the flowsheet make the flowsheet a viable abatement technique.
Keywords: Septic tanks; hydrolysis; anaerobic digestion; psychrophilic; nature-based solutions; carbon emissions